Efektifitas Model Pembelajaran Tipe Teams Accelerated Instruktion Dalam Meningkatkan Motivasi Belajar Dan Hasil Belajar Siswa - Maryani Maryani; Junaidi H. Matsum; Witarsa Witarsa (ICoTE Proceedings, 2019)
This study aims to identify the effectiveness of the learning model in the Cooperative Teaching Group (TAI) in improving the learning motivation and learning outcomes of the Class XI IS students in the MA Darussalam District of Mempawah Sengkubang. This study is a quantitative study with a quasi-experimental design (Quasi Experiment) research design. The population of this study was all students of XI IS class 93. The samples in this study were class X students of IS-1 as experimental classes and class X IS-2 as control class. The data in this study were processed by conclusion analysis. The results showed that the use of TAI's learning was effective in improving the motivation and learning outcomes of students in MA Darussalam, Mempawah District, Sengkubang.